Livelihood and Job Creation - Nagamatsu, Shingo (World Bank, Washington, DC, 2013)
Livelihood and job creation have long been critical challenges to disaster recovery. Following the Great East Japan Earthquake (GEJE), the Japanese government launched an innovative cash-for-work (CFW) project, hiring more than 31,700 jobless people to work not only on reconstruction, but also on clerical and support work for affected people. This allowed it to reach out to women and the elderly, vulnerable groups that were traditionally excluded from schemes focusing primarily on manual work. This report gives findings; lessons; and recommendations for developing countries.